Secure pairing of interface constrained devices. (24th February 2009) - Soriente, Claudio; Tsudik, Gene; Uzun, Ersin
Secure initial pairing of electronic gadgets is a challenging problem because of the usual lack of a common security infrastructure and the threat of so-called Man-in-the-Middle (MiTM) attacks. A number of techniques have been proposed to address the problem, but many are not applicable to devices lacking required interfaces, such as displays or speakers. In this paper, we introduce a new secure device pairing concept that involves using the human body either as the communication medium for – or the source of – the common secret. We implement the concept as a suite of practical pairing protocols for interface constrained devices.